(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: The study aims to assess Positive and Negative Syndrome Scale and analyzing the prescribing patterns among patients with schizophrenia at the Department of Psychiatry constitutes a prospective observational study. Materials and Methods: The study was conducted at the outpatient wards of the Psychiatry Departments at Government General Hospital, Guntur, Andhra Pradesh. It was designed as a prospective and observational study involving the collection of case sheets and medication records of patients, without the use of invasive techniques such as blood sample collection. The study spanned a 35-month period. Results and Discussion: The present study’s sociodemographic analysis such as revealed significant gender-based disparities in marital status, education, religion, occupation, and monthly income among the study participants was done. These findings align with previous studies that have highlighted the influence of sociodemographic factors on the well-being and functioning of individuals with schizophrenia status, education, and income have been recognized as determinants of quality of life and functioning in this population. These sociodemographic factors played a crucial role in shaping the unique challenges and needs of patients with schizophrenia. Conclusion: Our research study revealed that a comprehensive understanding of the subjects has the potential to enhance pharmacotherapy and contribute to a deeper comprehension of the pathogenesis of schizophrenia. In addition, we identified that managing negative symptoms in schizophrenia poses a significant challenge for psychiatric services. Expanding on the existing knowledge of schizophrenia provided valuable insights into sociodemographic factors, the positive, negative, and general psychopathology domains, as well as prescribing patterns affecting individuals with the disorder